Parallel Surfaces to Normal Ruled Surfaces of General Helices in the Sol Space Sol3 - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2013)
In this paper, parallel surfaces to normal ruled surface of general helices in the Sol(3) are studied. Also, explicit parametric equations of parallel surfaces to normal ruled surface of general helices in the Sol(3) are found.
Keywords: General helix; Sol Space; Normal surface; Parallelsurface